Rare Recurrent EWSR1-PLAGL1 Rearranged Intracranial Tumor With Biphasic Epithelioid Differentiation: One Case Report With Literature Review - Xing, Ai-yan; Yang, Wen-wei; Liu, Yu-lu; Sun, Nan-nan; Hao, Xiao-meng; Wang, Su-xia; Mu, Kun (Frontiers in Oncology, 2022)
EWSR1-rearranged tumors encompass a rare and heterogeneous group of entities with features of central nervous system (CNS) mesenchymal and primary glial/neuronal tumors. EWSR1-PLAGL1 gene fusion is a particularly rare rearrangement form. We present a recurrent intracranial EWSR1-PLAGL1 rearranged tumor and reviewed the relevant literature. Histopathology and immunohistochemistry (IHC) were evaluated of our case for both the primary and relapsed tumors. Fluorescence in situ hybridization (FISH) and next generation sequencing (NGS) were performed for the relapsed tumor. We compared the morphology, IHC results and molecular features with the reported EWSR1-PLAGL1 rearranged CNS tumors. Our case exhibited a unique feature with a variable biphasic pattern of epithelioid differentiation which differed from the two reported groups. Both the primary and relapsed tumors expressed cytokeratin of the focal area with epithelioid differentiation. The recurrent tumor presented with an increased proliferation index (average Ki67=15%) comparing with the primary tumor (average Ki67=5%). NGS showed TERT promoter mutation was the only molecular change besides EWSR1-PLAGL1 fusion. Our study provides further insight into intracranial tumors with EWSR1-PLAGL1 fusion, which represent a distinct CNS tumor with histological and immunohistochemical features not reported. Future studies, particular for the biphasic differentiation and the role of TERT promoter mutation were needed to clarify this rare rearranged tumor.